The Influence of Mutation, Compensation, and Promotion on The Motivation of Employees in The Ministry of Finance Jakarta With Turnover Intention As a Mediation Variable - Leni Andrayani; Deden Kurniawan (Greenation Research & Yayasan Global Resarch National, 2023)
Employees as part of Human Resources (HR) are called assets that play the most important role in achieving the goals of an institution. Employees are assets owned by an organization or institution, and many studies state that by providing mutations and compensation, employees will achieve the goals set by the organization and will be able to provide effective results and optimal performance. Therefore, there needs to be an assessment of the effect of mutation, compensation, and promotion on employee motivation at work. Based on these conditions, this study will discuss the effect of mutation, compensation, and promotions on employee motivation in the Ministry of Finance in Jakarta. Using a quantitative method, the research data was generated from a survey of 165 respondents.